1997
DOI: 10.1074/jbc.272.16.10853
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin E is a Novel Human Cysteine Proteinase Inhibitor with Structural Resemblance to Family 2 Cystatins

Abstract: A new member of the human cystatin superfamily, called cystatin E, has been found by expressed sequence tag (EST) sequencing in amniotic cell and fetal skin epithelial cell cDNA libraries. The sequence of a fulllength amniotic cell cDNA clone contained an open reading frame encoding a putative 28-residue signal peptide and a mature protein of 121 amino acids, including four cysteine residues and motifs of importance for the inhibitory activity of Family 2 cystatins like cystatin C. Recombinant cystatin E was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
141
2
3

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(150 citation statements)
references
References 42 publications
4
141
2
3
Order By: Relevance
“…Cystatin M, a potent inhibitor of human lysosomal proteases, was identified as a gene frequently transcriptionally downregulated during progression of breast cancer (Ni et al, 1997;Sotiropoulou et al, 1997;Zhang et al, 2004). In our study, we demonstrated that hypermethylation of the cystatin M promoter occurs frequently in primary breast carcinomas and breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cystatin M, a potent inhibitor of human lysosomal proteases, was identified as a gene frequently transcriptionally downregulated during progression of breast cancer (Ni et al, 1997;Sotiropoulou et al, 1997;Zhang et al, 2004). In our study, we demonstrated that hypermethylation of the cystatin M promoter occurs frequently in primary breast carcinomas and breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has been proposed that cystatin M may function as candidate tumour suppressor for breast carcinogenesis . Cystatin M is a potent inhibitor of cysteine peptidases, including papain, cathepsin B, cathepsin V and cathepsin L (Ni et al, 1997;Cheng et al, 2006). These peptidases play key roles in intracellular protein degradation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cystatin M (CST6) functions as an endogenous inhibitor of lysosomal cysteine proteases (Ni et al, 1997;Sotiropoulou et al, 1997), which are known to contribute to tumor cell invasion by degrading extracellular matrix components (Buck et al, 1992;Maciewicz et al, 1990;Mai et al, 2002). Cathepsin B and cathepsin L are two important cysteine proteases that have been implicated in tumor cell invasion and metastasis (Kane and Gottesman, 1990;Roshy et al, 2003;Slone et al, 1981).…”
Section: Introductionmentioning
confidence: 99%